The flaws in rent ceilings - Ryan Bourne (Institute of Economic Affairs (IEA), 2014)
Rent controls are probably the best researched and understood form of price control in economics. Their consequences are widely regarded as being extremely damaging and UK experience confirms this.In Britain, the period of rent controls between 1915 and 1989 was associated with the private rental sector collapsing from close to nine-tenths of the housing stock at the start of the 20th century to close to one-tenth by the late 1980s and early 1990s.When rents are held below market rates, outcomes can be expected to deteriorate over time. There is a substantial literature outlining the negative effects on the quality of rentable property, as well as substantial economic efficiency costs arising due to misallocation and lower labour mobility.Interest groups and politicians are now advocating what are known as 'second generation' rent controls, which entail rules governing increases in rents within a tenancy together with regulation of the length of tenancies.In the UK, the Labour Party has advocated such controls. Whilst there would be complete freedom for landlords to set rents between tenancies, rents within tenancies would be benchmarked so that increases are linked to average increases within a locality, some measure of inflation, or both during a three-year contract. Furthermore, tenants would have great security of tenure.Since rents can alter between tenancies, tenancy rent controls cannot improve affordability for any group other than in the very short term. It is most likely to simply change the timing of rent costs over a tenancy by raising initial rents. Indeed, the existence of these controls may even increase market rents overall as a result of greater regulatory uncertainty and the business risk of increased security of tenure raising the returns that landlords require.It is likely that these so-called tenancy rent controls will improve security for some tenants. However, this will come at a cost to other tenants. Experience suggests that landlords are more likely to treat tenants badly and lower their quality of service in other ways if security of tenure is enforced by law. Furthermore, there is no evidence that existing 'secure' contracts are unavailable in the UK when tenants are willing to pay for them.Some claim that these tenancy rent controls will not be damaging because they exist in Germany, where the market is regarded as a tenant-friendly environment. However, there are huge structural differences between Germany and the UK - not least that there is significantly more development of new dwellings in Germany, making rent levels much lower in general.Planning liberalisation would clearly be a welfare enhancing policy and would reduce the cost of living. Tenancy rent controls would not be welfare enhancing and are, if anything, likely to increase the cost of living. Tenancy rent controls would therefore be treating the symptoms of high rental costs to appease a particular interest group. The fact that the beneficiaries are obvious and well-organised whilst those who suffer are dispersed would make this is a potentially damaging policy, which could be very difficult to reverse.
Keywords: 330